gamma Heavy chain disease in man: cDNA sequence supports partial gene deletion model. - Alexander, A (1982)
Human gamma heavy chain disease (HCD) is characterized by the presence in serum of a short monoclonal Ig gamma chain unattached to light chains. Although most HCD proteins have internal deletions, in some the defect is NH2-terminal. The OMM gamma 3 HCD serum protein is of the latter type, having undergone an extensive NH2-terminal deletion with a sequence starting within the hinge. A cell line synthesizing the OMM protein has enabled us to study the biogenesis of the abnormal molecule. In vitro translation of isolated mRNA yields a protein containing a hydrophobic NH2-terminal leader sequence. In the intact cell, the precursor molecule is processed normally to yield a protein with an NH2-terminal sequence homologous to the beginning of the variable (V) region. The nucleotide sequence of cDNA prepared from the OMM mRNA encodes a 19-amino acid leader followed by the first 15 residues of the V region. An extensive internal deletion encompasses the remainder of the V and the entire CH1 domain. Immediately following the short V region, there is information in the cDNA for the entire normal hinge. The primary synthetic product is thus an internally deleted molecule that undergoes postsynthetic degradation to yield the NH2-terminally deleted serum protein. The structure of the OMM mRNA suggests that the protein abnormality results from a partial gene deletion rather than defective splicing.